Art-science-technology and systems of art in the age of digital culture: context Brazil (Palíndromo, 2014)
This paper proposes to approach the theme of art-science-technology in the age of digital culture from their relationships with the current system of art. For it, we relied upon interviews made available in the publication Art-science-technology: the art system in perspective (2014), which points out ways for the author’s doctoral research. In this opportunity, we analyze the Brazilian context in terms of production-distribution-consumption-preservation, in order to verify the insertion or not of the production, also nominated as digital art in the contemporary art system. From this analysis, we propose a reflection about the systems of art in contemporaneity and the possibility of existence of a particular system for art-science-technology in dialogue with the contemporary art system, but especially with the culture of the early twenty-first century.
Keywords: art-science-tecnhology; digital art; digital culture; art system